A Multifunctional Biomimetic Flexible Sensor Based Novel Artificial Tactile Neuron with Perceptual Memory. Issue 23 (10th November 2021) - Xia, Qing; Qin, Yuxiang; Zheng, Anbo; Qiu, Peilun; Zhang, Xueshuo
Abstract: The bio‐inspired sensory memory device functions as a multifunctional artificial perceptual learning system that can effectively analyze and retain multiple sensory signals. In this work, the multiscale hierarchical surface of reed leaves is templated to prepare CNTs/PDMS films, and a new type of electronic skin (E‐skin) is constructed. Due to its unique multi‐scale sensing layer surface, E‐skin exhibits a wide pressure detection range and ultrahigh sensitivity (235.95 kPa −1 ) and linearity (0.99 under 1.95–12.4 kPa). The memristor serving as artificial synapse is formed with HfO2 film as resistive switch layer, which has remarkable uniformity, large memory window of 10 2 and excellent plasticity. After integration of E‐skin with artificial synapse, the artificial synapse could be activated by the electrical information from the E‐skin to generate excitatory postsynaptic currents and the pressure information could be well retained by the memristor element. An artificial tactile perceptual neuron system with excellent retention performance, good stability and accurately recognition memory is realized, and meanwhile, the accurate decoding of Morse code by recognizing external pressure is realized. The present work transduces the concept of carbon‐based biology into a silicon‐based electronic device, which is of great significance to the development of hardware architecture in artificial intelligence. Abstract : An artificial tactile perceptual neuron system is proposed by coupling a unique hierarchical micro‐nanostructured CNTs/PDMS piezoresistive sensor with an HfO2 ‐based sandwich‐structured memristor. The tactile sensor‐memristor coupling with excellent retention performance, good stability and accurately recognition memory is realized, and meanwhile, the accurate decoding of Morse code by recognizing external pressure is realized.